Improvement of the bill pf materials (BOM) generator for product variants. - Raharno,Sri (Asean Engineering Journal)
In short, a bill of materials (BOM) is a list of parts or components and quantities, which are required to manufacture a product. A BOM also describes the component structure of a product, usually as a hierarchical structure implemented within a relational database. Generally, to generate a BOM of a product that has no variant is a relatively simple process. On the other hand, there are problems in generating a BOM for a product with many variants. Since the number of variants may be large, it is impossible to design and maintain a BOM structure for each variant.The high number of components will certainly results in a time consuming BOM generation. Moreover, another challenge of data management associated with variety of products is data redundancy. Inorder to overcome the problems, previous research has developed a product data model using a single structure for many product variants. The research also has implemented a heuristic rule as a BOM generator. However, the implementation has shown that generating a BOM has been time consuming and required relatively complex codes. This research deals with an improvement of the BOM generator developed in previous research. The improvement involves reducing the duration of processes and simplifying the codes.